Women’s Agency and Resistance to Cyber Flashing on Twitter - Athirah, Shafa; Hidayana, Irwan M. (UI Scholars Hub, 2023)
This article explores the specific forms of online sexual harassment that has been on the rise since Covid-19 pandemic, namely cyber flashing, and how women respond to such practice on social media. Digital ethnography. which included in-depth interview with victims of cyber flashing, was conducted to dive deep into women’s cyber flashing experiences on Twitter. Authors argue that women make sense of their cyber flashing experiences, including tangible impacts on women, and exercise their agency through the acts of public and quiet resistance. The results showed that women carry out various acts of resistance such as ‘spill’ tweet, ‘warning’ tweet, demeaning DM respond, block and report perpetratos’ accounts, story retelling, as well as changing online identity. Women exercise their agency through acts of resistance in order to create a safe space for themselves in Twitter platform.